Softening of the flux-line structure in La1.8Sr0.2CuO4 measured by a vibrating reed - Rodriguez, E.; Luzuriaga, J.; Dovidio, C.A.; Esparza, D.A. (American Physical Society, 1990)
Fil: Rodriguez, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina